Influence of light-emitting diodes on the efficiency of valuable woody plants micropropagation (International Journal of Biology and Chemistry, 2023)
The article presents the results of studying the effect of light-emitting diodes (LEDs) on the efficiency of micropropagation of valuable woody plants. Commercial use of micropropagation requires optimization of various parameters, including light quality and lighting regime. Nowadays, LED have become an alternative source of illumination for plant tissue culture, including woody plants. Recently, along with medicinal herbaceous plants, tree crops have also become widely used as a source of various pharmaceuticals. Therefore, it is promising to optimize the technology of micropropagation for the rapid and massive production of valuable woody plants. The current research focused on analysing the effects of different LEDs on Paulownia sp. micropropagation: white (W), red (R), blue (B), mixed red and blue (R:B), and the Fitotron climate chamber. The fluorescent light was used as a control. Micropropagation efficiency was evaluated using the following parameters: height, number of axillary buds, length of internodes, number and length of roots, and photosynthetic pigment content. P. tomentosa produced the greatest number of roots under R LEDs, while hybrid Paulownia Sieb.Zucc. × Elongata - under W and R LEDs. In hybrid Paulownia Sieb.Zucc. × Elongata, the most intense leaf and internode formation was observed under R:B and R LEDs. The content of chlorophyll a and b in P. tomentosa leaves was significantly higher under R LED, while in HP leaves - under B LED. The obtained results are an important contribution to the commercial use of Paulownia and other valuable woody plants for mass production of plant material with biologically active properties.